Visible Light-Generated Antiviral Effect on Plasmonic Ag-TiO2-Based Reactive Nanocomposite Thin Film - Boldogkői, Zsolt; Csabai, Zsolt; Tombácz, Dóra; Janovák, László; Balassa, Lilla; Deák, Ágota; Tóth, Péter S.; Janáky, Csaba; Duda, Ernő; Dékány, Imre (Frontiers in Bioengineering and Biotechnology, 2021)
The recent coronavirus pandemic pointed out the vulnerability of humanity to new emerging infectious diseases. Experts warn that future pandemics may emerge more frequently with greater devastating effects on population health and the world economy. Although viruses are unable to propagate on lifeless surfaces, they can retain their infectivity and spread further on contact with these surfaces. The objective of our study is to analyze photoreactive composite films that exert antiviral effects upon illumination. Reactive plasmonic titanium dioxide-based polymeric nanocomposite film was prepared with a thickness of 1-1.5 µm, which produces reactive oxygen species (ROS) under visible light irradiation (λ ≥ 435 nm). These species are suitable for photooxidation of adsorbed organic molecules (e.g. benzoic acid) on the nanocomposite surface. Moreover, high molecular weight proteins are also degraded or partially oxidized in this process on the composite surface. Since the Ag0-TiO2/polymer composite film used showed excellent reactivity in the formation of OH• radicals, the photocatalytic effect on high molecular weight (M=~66.000 Da) bovine serum albumin (BSA) protein was investigated. Given that changes in the structure of the protein were observed upon exposure to light, we assumed virucidal effect of the illuminated photoreactive composite film. We tested this hypothesis using an airborne-transmitted herpesvirus. As a result, we obtained a drastic decrease in infection capability of the virus on the photoreactive surface compared to the control surface.